Characterization labile and stable nitrogen - Westerhof, R; Vilela, Lourival; Ayarza, Miguel Angel; Zech, W. (International Center for Tropical Agriculture, 1999)
The permanganate oxidation procedure is easily performed and may help monitor large areas for their soil organic matter (SOM) quality and nitrogen (N) availability. Knowledge of the chemical characteristics of fractions that are lost or remain after oxidation will help explain results obtained by this method. We found that amino acid N contributed 22.7% to the permanganate-extractable N fraction (PEN) and amino sugar N 9. 1 %, but the remaining 68.2% of the PEN was of "unknown" N. Stable N had lower amounts of amino acid N (15.5%) and amino sugar N (6.2%). Permanganate-extractable N and stable N may be spatially separated, that is, PEN is found outside microaggregates, whereas stable N is inside, where it is protected from permanganate extraction and probably also from microbial breakdown. Together with physically protected N, the stable N fraction also contained an important amount of chemically recalcitrant, not-extractable, "unknown" N with a chemical composition that is hypothesized to be different from that of the permanganate-extractable "unknown" N.